Low emotional response to traumatic footage is associated with an absence of analogue flashbacks: An individual participant data meta-analysis of 16 trauma film paradigm experiments. - Clark, I; Mackay, C; Holmes, E (Routledge, 2014)
Most people will experience or witness a traumatic event. A common occurrence after trauma is the experience of involuntary emotional memories of the traumatic event, herewith "flashbacks". Some individuals, however, report no flashbacks. Prospective work investigating psychological factors associated with an absence of flashbacks is lacking. We performed an individual participant data meta-analysis on 16 experiments (n = 458) using the trauma film paradigm to investigate the association of emotional response to traumatic film footage and commonly collected baseline characteristics (trait anxiety, current depression, trauma history) with an absence of analogue flashbacks. An absence of analogue flashbacks was associated with low emotional response to the traumatic film footage and, to a lesser extent, low trait anxiety and low current depression levels. Trauma history and recognition memory for the film were not significantly associated with an absence of analogue flashbacks. Understanding why some individuals report an absence of flashbacks may aid preventative treatments against flashback development.